The Role of Christian Theology in Pluralism and Secularism in The Era of Globalization - Radius Simanjuntak; Rusdi Fatolosa Zebua; Geto Geto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This article examines the role of Christian theology in dealing with pluralism and secularism in the era of globalization. The era of globalization is marked by an increasing plurality of religions, cultures, and various perspectives on life that in many ways are moving away from a theocentric perspective. In that context, Christian theology is faced with the responsibility to be present as a reflective and transformative force that carries messages of peace, truth, and certainty of faith. This research aims to explore the role of Christian theology in an increasingly pluralistic society and influenced by the currents of secularism that have the potential to erode the values of faith. The method used is a literature study by analyzing various literature related to the concept of Christian theology, the impact of secularism on the life of faith, and various relevant theological responses in dealing with these challenges. The results of the study show that inclusive theological education, a conciliatory approach in interreligious relations, a holistic transformation of church life, and the active participation of the church in social service are concrete forms of the contribution of Christianity in a pluralistic society. Through this approach, Christian theology functions not only as a doctrinal framework, but also as a praxis that presents the values of the Kingdom of God in social life.